A southern perspective on development studies: contributions from Latin America - Mallorquin, Carlos (Cinta de Moebio. Revista de Epistemología de Ciencias Sociales, 2017)
The article offers a synthesis of Latin American economic thought post-second world war, underlining in particular the specificity of the regional perspective. The idea is to describe their beginnings and key regional authors, which is generally unknown in Anglo-Saxon academic circles. The reading that guides the presentation questions Eurocentric interpretations. Since the 1980 economic discourse in Latin America has lost its sui generis characteristics, its vocabulary today has been lost to the new generations, given the pre-eminence of orthodox neoliberal ideas and policies which certainly have not improved the living standards of the region.